Mencari Pola Baru Hubungan Negara-Rakyat - Purwo Santoso (Jurnal Ilmu Sosial dan Ilmu Politik, 2000)
This article is ment to be the introduction to the special edition of this Journal. It outlines the discussion on the issue of violent and empowerment within the context of institutionalising a democratic governance in Indonesia. It envisioned a more indirect style of governance through a systematic reform inspired by the working of market mechanism. Institutionalisation of democratic governance requires not only empowered people but also capability for systematically transforms the energy for winning a conflict into a healthy competition